Budaya Konsumerisme Pekerja Kafe di Wilayah Jember Kota - Soemarsono, Anisa Andiana Wulandari; Vernanda, Hana; Roselawati, Lisa; Safitri, Ajeng Cahya (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
Consumption essentially becomes a necessity to be fulfilled in society. Over time, the concept of consumption has become more complex. One aspect of this complexity is consumption in the postmodern era, which tends to be used as a symbol of identity and a marker of lifestyle for a community or individual. Society has become unable to distinguish between needs and desires. This has led to the emergence of a new phenomenon known as consumerism. This phenomenon has spread and influenced all classes. Its impact can affect both social and economic aspects. Café workers are among those affected by this culture of consumerism. In short, the pressure arising from the influence of media and modernization creates a sense of individual need to conform to the standards and lifestyles constructed within society. Therefore, the aim of this study is to understand how the culture of consumerism affects café workers in Kebonsari Village, Jember Regency, using a qualitative approach through observation and interviews.